Conservative management of gunshot oesophageal injuries: A report of two consecutive exceptional cases - Francesco Virdis; Sharfuddin Chowdhury; Andrew John Nicol; Pradeep Harkison Navsaria (African Journal of Emergency Medicine, 2016)
Oesophageal trauma carries high mortality and morbidity. For penetrating intrathoracic oesophageal injury, surgical repair has been the standard for decades to avoid its devastating consequences. Case report: Both patients presented with a thoracoabdominal gunshot wound and retained intraabdominal missile. Although there were no visible signs of perforation on oesophagoscopy or contrast swallow, the presence of an intraluminal bullet highly suggested a thoracic oesophageal injury. Discussion: Non-operative management of intrathoracic oesophageal perforation is controversial. Small perforations or contained leaks diagnosed within 24–48 h in a stable patient with no mediastinitis or empyema can be managed non-operatively with antibiotics and nasogastric feeds. These two case reports support the notion of selective non-operative management of asymptomatic patients with penetrating injury to the oesophagus.